(untitled) (Shahroud Journal of Medical Sciences, 2020)
Background Low Birth Weight (LBW) is one of the most important health indicators and is one of the most important causes of infant mortality. This study was conducted to investigate the effect of family socioeconomic status (SES) on LBW in Shahroud. Methods In this cross sectional study, 4242 neonates were entered in the study. Data gathering tool was a valid and reliable questionnaire and also we use electronic records of household’s health profile to complete data collection Form. Determinants of household’s SES were 10 economic factors, including household assets like; car ownership, computer and Internet access, microwave, cooking place, number of residential house rooms, type of heating and cooling equipment, bathroom in the house, mother’s history of foreign travel-tourism and for social factors there were 4 variables; father's education, mother's education, father's job and number of children. The logistic regression model was used by controlling the confounding variables to investigate the effect of socioeconomic factors on LBW. Results Among study subjects, 312 (7.4 %) of them were LBW (CI 95%=6.6-8.1). The chance of low birth weight in neonates with low socioeconomic group was 2.6 times more than high class group (95% CI= 3.47 - 2.01). Conclusion The quality of health services and the improvement of the socio-economic situation must be taken into account to reduce the inequity of LBW between poor and rich family neonates. (Keywords): Neonate, Socioeconomic status, Low Birth Weight, Shahroud.